PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI VILLA KUBU MANGGALA SEMINYAK - cahyadi, Made Satwika Dwi; Honor satrya, I Gusti Bagus (E-Jurnal Manajemen; Vol 7 No 2 (2018), 2018)
One of the factors that must be considered in managing human resources is the volunteerism of employees in helping co-workers outside of their responsibilities (Organizational Citizenship Behavior). The symptoms of problems associated with low OCB are due to the low transformational leadership and organizational commitment. The purpose of this study was to determine the effect of transformational leadership and organizational commitment to OCB at Villa Kubu Manggala Seminyak. This research was conducted at Villa Kubu Manggala Seminyak by using census method that is 30 respondents. The data was collected by distributing questionnaires using a 5-point likert scale to measure 12 statement items. Tests conducted using the classical assumption test that is normality test, multicollinearity test, heteroscedasticity test, f test and t test. The results of the analysis show that transformational leadership has a positive and significant effect on OCB and organizational commitment has a positive and significant impact on OCB. To improve the OCB's behavior within the organization, companies should pay more attention to normative commitment and promotion opportunities.